Urgensi Literasi Media Digital melalui Pendidikan sebagai Upaya Mitigasi Disinformasi di Ruang Media Sosial - sigit purnomo; Heri Gunawan; Fauzan Haryono (CV. ITTC INDONESIA, 2026)
The rapid growth of social media has opened significant opportunities for the spread of disinformation, particularly among students who are active yet vulnerable users of digital platforms. This study aims to examine the condition of students' digital media literacy, the patterns and characteristics of disinformation spread, and the urgency and role of education in building critical thinking skills as a strategy to mitigate disinformation in social media spaces. This research employs a qualitative approach using the library research method, with data obtained through the exploration, review, and content analysis of relevant journal articles, books, and official reports. The findings indicate that students' digital literacy levels remain in the moderate-to-low category, with notable gaps across educational levels and regions, and that information evaluation skills remain weaker than technical device proficiency. The pattern of disinformation spread among students is influenced by psychological factors, platform algorithms, and a weak culture of information verification. This study affirms that strengthening digital literacy through formal education is an urgent necessity and a more sustainable strategy than short-term literacy campaigns, as it can systematically build students' critical thinking skills through the synergy of curriculum, teacher competence, and a supportive learning environment. The novelty of this study lies in positioning formal education as the primary and sustainable pathway for mitigating disinformation, distinguishing it from previous studies that tend to examine digital literacy and disinformation separately.